Impacts of the COVID-19 pandemic on food systems in Manitoba, Canada and ways forward for resilience: a scoping review - Lowitt, Kristen; Slater, Joyce; Rutta, Evodius (Frontiers in Sustainable Food Systems, 2024)
Various studies over the past 3 years have synthesized trends and impacts of the COVID-19 pandemic on Canada’s national food system. However, less research has characterized the effects of COVID-19 within regional and provincial food system contexts. This article presents results from a scoping review of peer-reviewed and grey literature published from March 2020 until end of March 2023 examining the impacts of the COVID-19 pandemic on food systems in the province of Manitoba, Canada. Findings are presented according to the categories of food security funding, policy, and programming; individual and household food security; and food systems. In each area we synthesize key findings and discuss their significance in relation to existing food systems scholarship and national trends. Using review results, we propose priority areas for research and practice to support equitable and resilient food systems in Manitoba, including: (1) undertaking evaluation of food system policies, programs, and funding implemented during the pandemic (2) enhancing food security monitoring for vulnerable populations (3) further exploring community experiences and responses to food security, and (4) examining opportunities for local food systems development.